A regenerative approach towards mucosal fenestration closure. (6th June 2013) - Gandi, Padma; Anumala, Naveen; Reddy, Amarender; Viswa Chandra, Rampalli
Abstract : Mucosal fenestration is an opening or an interstice through the oral mucosa. A lesion which occurs with greater frequency than generally realised, its occurrence is attributed to a myriad of causes. Mucogingival procedures including connective tissue grafts, free gingival grafts and lateral pedicle grafts are generally considered to be the treatment of choice in the closure of a mucosal fenestration. More often, these procedures are performed in conjunction with other procedures such as periradicular surgery and with bone grafts. However, the concomitant use of gingival grafts and bone grafts in mucosal fenestrations secondary to infections in sites exhibiting severe bone loss is highly debatable. In this article, we report two cases of mucosal fenestrations secondary to trauma and their management by regenerative periodontal surgery with the placement of guided tissue regeneration membrane and bone graft. The final outcome was a complete closure of the fenestration in both the cases.